2009
DOI: 10.1111/j.1365-3040.2009.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of sorghum axillary bud outgrowth by shade, phyB and defoliation signalling pathways

Abstract: In recent years, several genetic components of vegetative axillary bud development have been defined in both monocots and eudicots, but our understanding of environmental inputs on branching remains limited. Recent work in sorghum (Sorghum bicolor) has revealed a role for phytochrome B (phyB) in the control of axillary bud outgrowth through the regulation of Teosinte Branched1 (TB1) gene. In maize (Zea mays), TB1 is a dosage-dependent inhibitor of axillary meristem progression, and the expression level of TB1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 96 publications
(203 reference statements)
10
134
0
1
Order By: Relevance
“…Studies on bud dormancy induced by apically derived auxin in pea and dormancy induced by shade signals and defoliation in sorghum have documented downregulation of cell division-related genes in dormant buds (Devitt and Stafstrom, 1995;Kebrom et al, 2010). However, results from other systems indicated that not all types of dormancy are associated with downregulation of the expression of cell cycle-related genes (Espinosa-Ruiz et al, 2004;Kebrom et al, 2010).…”
Section: Expression Of Cell Cycle-related Genes In Dormant Buds Of Tinmentioning
confidence: 86%
See 3 more Smart Citations
“…Studies on bud dormancy induced by apically derived auxin in pea and dormancy induced by shade signals and defoliation in sorghum have documented downregulation of cell division-related genes in dormant buds (Devitt and Stafstrom, 1995;Kebrom et al, 2010). However, results from other systems indicated that not all types of dormancy are associated with downregulation of the expression of cell cycle-related genes (Espinosa-Ruiz et al, 2004;Kebrom et al, 2010).…”
Section: Expression Of Cell Cycle-related Genes In Dormant Buds Of Tinmentioning
confidence: 86%
“…However, results from other systems indicated that not all types of dormancy are associated with downregulation of the expression of cell cycle-related genes (Espinosa-Ruiz et al, 2004;Kebrom et al, 2010). Hence, the induction of different types or degrees of bud dormancy may involve distinct molecular mechanisms depending on the dormancy-inducing factors.…”
Section: Expression Of Cell Cycle-related Genes In Dormant Buds Of Tinmentioning
confidence: 99%
See 2 more Smart Citations
“…2A) Kebrom et al, 2006Kebrom et al, , 2010. After 6 DAP, the buds in phyB-1 plants show no or very slow growth, whereas buds of wild-type plants continue to steadily increase in size ( Fig.…”
Section: Resultsmentioning
confidence: 99%